2018
DOI: 10.1002/polb.24618
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of helical microfibers from melt blown polymer blends

Abstract: Helical fibers in micro/nanoscale resembling plant tendrils have been of increasing interest due to their unique characteristics. Fabrication of helical microfibers from polymer blends using melt blowing technique is reported in this study. An elastomeric and a stiff polymer are chosen as the raw materials, and a designed swirl-die melt-blowing device is used to prepare the microfibrous nonwovens. Focusing on the interfacial interaction between the polymer components induced by the polymer structure and intrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…Deng N. et al [9] showed that utilization of the incompatible blend system (namely mixture of PP and PS) can increase fiber diameter variation considerably due to continues fluctuation of blend viscosity during MB process as visible in Figure 19. Creation of even helical microfibers with a three-dimensional spiral shape from polypropylene (PP)/thermoplastic polyurethane (TPU) incompatible blend was also reported [169] (see Figure 20).…”
Section: Please Cite This Article As Doi:101063/15116336mentioning
confidence: 89%
“…Deng N. et al [9] showed that utilization of the incompatible blend system (namely mixture of PP and PS) can increase fiber diameter variation considerably due to continues fluctuation of blend viscosity during MB process as visible in Figure 19. Creation of even helical microfibers with a three-dimensional spiral shape from polypropylene (PP)/thermoplastic polyurethane (TPU) incompatible blend was also reported [169] (see Figure 20).…”
Section: Please Cite This Article As Doi:101063/15116336mentioning
confidence: 89%
“…Schematics of the (a) swirl‐die melt‐blowing setup, (b) end‐on view of the swirl die. (for further details, see paper by Li et al), (c) auxiliary device, and (d) SEM images of the helical microfiber and the cross‐section. The right images are the partial enlargement of (d).…”
Section: Experimental and Simulationmentioning
confidence: 99%
“…Each air orifice has a die angle and a twist angle (see ref . for detailed description of the swirl die).…”
Section: Experimental and Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Melt-blown microfibers with a mean diameter of several micrometers are obtained by attenuating the polymeric melt jets with the help of a high-speed air stream [1], and the melt-blown micro-fibrous materials are widely used in areas of filtration and oil/water separation [2,3]. Recently, functional fibers, such as melt-blown cross-linked or helical fibers, have emerged [4,5], which are expected to have great potential applications.…”
Section: Introductionmentioning
confidence: 99%